2019
DOI: 10.1101/622324
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chlamydia trachomatisoutbreak: when the virulence-associated genome backbone imports a prevalence-associated major antigen signature

Abstract: Chlamydia trachomatisis the most prevalent sexually transmitted bacteria worldwide and the causative agent of blinding trachoma. Strains are classified based onompAgenotypes, which are strongly linked with differential tissue tropism and disease outcomes. A lymphogranuloma venereum (LGV) epidemics, characterized by ulcerative proctitis, has emerged in the last two decades (mainly L2b genotype), raising high concern especially due to its circulation among men who have sex with men (MSM). Here, we report an ongo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…UniProtKB or Pfam-A database). Further gene and protein sequence homology or conserved domain analyses are commonly performed in chlamydial WGS annotation studies utilising publicly available or custom databases (Voigt et al, 2012;Read et al, 2013;Borges and Gomes, 2015;Seth-Smith et al, 2017a;Borges et al, 2019;Sigalova et al, 2019;Hölzer et al, 2020;Heijne et al, 2021;White et al, 2021). Recently, Pillonel and colleagues developed "openaccess ChlamDB", a comparative genomics database containing 277 genomes covering the entire Chlamydiae phylum as well as their closest relatives belonging to the Planctomycetes-Verrucomicrobiae-Chlamydiae (PVC) superphylum.…”
mentioning
confidence: 99%
“…UniProtKB or Pfam-A database). Further gene and protein sequence homology or conserved domain analyses are commonly performed in chlamydial WGS annotation studies utilising publicly available or custom databases (Voigt et al, 2012;Read et al, 2013;Borges and Gomes, 2015;Seth-Smith et al, 2017a;Borges et al, 2019;Sigalova et al, 2019;Hölzer et al, 2020;Heijne et al, 2021;White et al, 2021). Recently, Pillonel and colleagues developed "openaccess ChlamDB", a comparative genomics database containing 277 genomes covering the entire Chlamydiae phylum as well as their closest relatives belonging to the Planctomycetes-Verrucomicrobiae-Chlamydiae (PVC) superphylum.…”
mentioning
confidence: 99%
“…While RNA "baits" acted upon complex biological samples (in this case, a homogenate of liver and spleen), potentially capturing the in vivo genomic diversity of the strain, sequencing from culture reflects only the diversity of one or a few colonies. This approach has been previously applied for other pathogens, such as Treponema pallidum, revealing substantial within-patient genetic diversity (Pinto et al, 2016), Mycobacterium tuberculosis, as an alternative approach for surveillance and drug susceptibility inferences (Macedo et al, 2023), and Chlamydia trachomatis, where the technique was used to characterize and monitor the transcontinental dissemination of an emergent recombinant strain (Borges et al, 2021). In this context, despite F. tularensis being a highly monomorphic pathogen, the TCE approach allows the exploration of this additional layer of genetic variability of low-frequency populations and potentially distinguish isolates that are otherwise indistinguishable (if only the consensus sequences are considered).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel to culture attempts, we used the designed RNA oligonucleotide baits in order to capture and sequence F. tularensis genomes directly from the biological samples, similarly to previous studies (Pinto et al, 2016;Borges et al, 2021;Macedo et al, 2023). After DNA extraction (described above), whole-genome capture and sequencing of Francisella tularensis was performed following SureSelect XT HS Target Enrichment System for Illumina Multiplexed Sequencing protocol (G9702-90000, Version E0, November 2020, Agilent Technologies, Santa Clara, CA, United States) using the custom baits library described above, in a 1:5 dilution.…”
Section: Sureselect Xt Hs Targeted Whole-genome Sequencing Of Francis...mentioning
confidence: 99%
“…The ompA gene of C. trachomatis can be inserted into different genomic backbones through potential gene recombination. However, the recombination of ompA may happen most likely between L strain and I/J/K strains or between ocular and urogenital branches or between L2b and D-Da strains (Somboonna et al, 2011;Harris et al, 2012;Matičič et al, 2016;Borges et al, 2021). Hadfield et al (2017) reported that in their comprehensive global genome dynamic analysis of C. trachomatis, only serovar D and J appeared in both monophyletic lineage T1 and T2.…”
Section: Discussionmentioning
confidence: 99%